Polyphenol oxidase dominates the conversions of flavonol glycosides in tea leaves. (1st March 2021) - Guo, Xiao-Yuan; Lv, Yi-Qing; Ye, Ying; Liu, Ze-Ye; Zheng, Xin-Qiang; Lu, Jian-Liang; Liang, Yue-Rong; Ye, Jian-Hui
Highlights: PPO was more active in catalysing flavonol glycosides than POD and β-glucosidase. PPO activity was greatly influenced by pH but moderately impacted by temperature. POD strongly promoted the PPO-induced oxidation of flavonol glycosides. Aglycone was the dominant moiety for the sensitivity of flavonol glycosides to PPO. Sugar moiety promoted the better docking between flavonol glycosides and PPO. Abstract: Flavonol glycosides are associated with astringency and bitterness of teas. To clarify the dominant enzymatic reaction of flavonol glycosides in tea leaves, the catalytic effects of polyphenol oxidase (PPO), peroxidase (POD) and β-glucosidase were studied, with the maintaining rates of total flavonol glycosides (TFG) being 73.0%, 99.8% and 94.3%. PPO was selected for further investigations, including the effects of pH value (3.5 6.5), temperature (25 °C 55 °C) and dosage (39 72 U/mL PPO and 36 U/mL PPO, 3 36 U/mL POD). The oxidation of flavonol glycosides were intensified at pH 6.5, with 51.8% and 15.4% of TFG maintained after PPO and PPO + POD treatments, suggesting an enhancement from POD. The sensitivity ranking to PPO was: myricetin glycosides > quercetin glycosides > kaempferol glycosides. The inhibitor treatment testified the leading role of PPO in catalyzing flavonol glycosides in tea leaves. Sugar moiety enhanced the docking affinity of flavonol glycosides for PPO. PPO shows the potential of modifying flavonol glycoside composition.